Cerebral responses and role of the prefrontal cortex in conditioned pain modulation: an fMRI study in healthy subjects - Bogdanov, Volodymyr B.; Viganò, Alessandro; Noirhomme, Quentin; Bogdanova, Olena V.; Guy, Nathalie; Laureys, Steven; Renshaw, Perry F.; Dallel, Radhouane; Phillips, Christophe; Schoenen, Jean (Behavioural brain research, 2015)
•The mechanisms underlying conditioned pain modulation are multifaceted.•During cold, application-specific cerebral activations were found in precuneus and left insula.•Conditioned suppression of insula test-pain response was related to hypoalgesia.•The insular changes are predicted by early prefrontal response to cold conditioning.•Smaller early prefrontal response predicts heterotopic noxious hyperalgesia. The mechanisms underlying conditioned pain modulation (CPM) are multifaceted. We searched for a link between individual differences in prefrontal cortex activity during multi-trial heterotopic noxious cold conditioning and modulation of the cerebral response to phasic heat pain. In 24 healthy female subjects, we conditioned laser heat stimuli to the left hand by applying alternatively ice-cold or lukewarm compresses to the right foot. We compared pain ratings with cerebral fMRI BOLD responses. We also analyzed the relation between CPM and BOLD changes produced by the heterotopic cold conditioning itself, as well as the impact of anxiety and habituation of cold-pain ratings. Specific cerebral activation was identified in precuneus and left posterior insula/SII, respectively, during early and sustained phases of cold application. During cold conditioning, laser pain decreased (n=7), increased (n=10) or stayed unchanged (n=7). At the individual level, the psychophysical effect was directly proportional to the cold-induced modulation of the laser-induced BOLD response in left posterior insula/SII. The latter correlated with the BOLD response recorded 80s earlier during the initial 10-s phase of cold application in anterior cingulate, orbitofrontal and lateral prefrontal cortices. High anxiety and habituation of cold pain were associated with greater laser heat-induced pain during heterotopic cold stimulation. The habituation was also linked to the early cold-induced orbitofrontal responses. We conclude that individual differences in conditioned pain modulation are related to different levels of prefrontal cortical activation by the early part of the conditioning stimulus, possibly due to different levels in trait anxiety.